2009
DOI: 10.1002/hbm.20826
|View full text |Cite
|
Sign up to set email alerts
|

Functional integration within the human pain system as revealed by Granger causality

Abstract: Pain is a complex experience subserved by an extended network of brain areas. However, the functional integration among these brain areas, i.e., how they interact and communicate to generate a coherent pain percept and an adequate behavioral response is largely unknown. Here, we used magnetoencephalography to investigate functional integration among pain-related cortical activations in terms of Granger causality and compared it with tactile-related activations. The results show causal influences of primary som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…Importantly, two spatiotemporal features could be appreciated when comparing the significant modulation of sMMN and nMMN (see Figures and , left panel, first two graphs from top): (1) The amplitude modulation of the sMMN had an earlier onset than the nMMN both at the contralateral temporal region (SEP‐M‐tROI a: 110 ms vs. NEP‐M‐tROI a: 182 ms) and ipsilateral temporal region (SEP‐M‐tROI d: 162 ms vs. NEP‐M‐tROI c: 186 ms)—a finding that is fully compatible with the conduction velocity of somatosensory Aβ and nociceptive Aδ fibers (Ploner, Schmitz, Freund, & Schnitzler, , ), respectively. (2) The difference of latency between the contralateral and the ipsilateral onset of activity was larger for the sMMN than for the nMMN (52 ms vs. 4 ms), thus supporting the notion that nociceptive processing is faster than tactile processing in the human brain; that is, somatosensory inputs are processed in a serial fashion (e.g., Hu, Zhang, & Hu, ) whereas the nociceptive inputs are processed in a parallel manner (Liang, Mouraux, & Iannetti, ; Ploner, Gross, Timmermann, & Schnitzler, ; Ploner, Schoffelen, Schnitzler, & Gross, ). Crucially, as the topographies of these responses largely overlapped, latency discrepancies are the main salient differences between sMMN and nMMN.…”
Section: Discussionmentioning
confidence: 61%
“…Importantly, two spatiotemporal features could be appreciated when comparing the significant modulation of sMMN and nMMN (see Figures and , left panel, first two graphs from top): (1) The amplitude modulation of the sMMN had an earlier onset than the nMMN both at the contralateral temporal region (SEP‐M‐tROI a: 110 ms vs. NEP‐M‐tROI a: 182 ms) and ipsilateral temporal region (SEP‐M‐tROI d: 162 ms vs. NEP‐M‐tROI c: 186 ms)—a finding that is fully compatible with the conduction velocity of somatosensory Aβ and nociceptive Aδ fibers (Ploner, Schmitz, Freund, & Schnitzler, , ), respectively. (2) The difference of latency between the contralateral and the ipsilateral onset of activity was larger for the sMMN than for the nMMN (52 ms vs. 4 ms), thus supporting the notion that nociceptive processing is faster than tactile processing in the human brain; that is, somatosensory inputs are processed in a serial fashion (e.g., Hu, Zhang, & Hu, ) whereas the nociceptive inputs are processed in a parallel manner (Liang, Mouraux, & Iannetti, ; Ploner, Gross, Timmermann, & Schnitzler, ; Ploner, Schoffelen, Schnitzler, & Gross, ). Crucially, as the topographies of these responses largely overlapped, latency discrepancies are the main salient differences between sMMN and nMMN.…”
Section: Discussionmentioning
confidence: 61%
“…Contrary to this study, an earlier study has reported the significant GRC between S1 and SII (part of PS) in response to a tactile but not a painful laser stimulus in healthy subjects carrying out a reaction time task [81]. In that study, responses were magnetic signals that were projected upon maps derived from source analysis of activity recorded during sensory and motor tasks.…”
Section: Discussionmentioning
confidence: 65%
“…This leads to an interesting possibility: that S1 could be specifically involved in the detection of changes in non-nociceptive somatosensory input, whereas the anterior insula could be specifically involved in the detection of changes in nociceptive somatosensory input. This difference in the cortical processing of nociceptive and non-nociceptive sensory inputs could be related to the results of previous studies suggesting that ascending non-nociceptive somatosensory thalamocortical input projects primarily to the contralateral S1 [Gardner and Kandel, 2000;Hu et al, 2012;Iwamura, 1998], whereas ascending nociceptive somatosensory thalamocortical input predominantly projects to other brain structures such as insular and cingulate cortices [Frot et al, 2008;Inui et al, 2004;Ploner et al, 2009]. Importantly, our observation does not rule out other possible functions of the anterior insula in nociceptive processing [e.g., representation of prediction error; Seymour et al, 2005].…”
Section: Figurementioning
confidence: 60%